Investigating the association between dairy intake and migraine odds among pediatrics and adolescents: A case-control study - Ariyanfar, Shadi; Razeghi Jahromi, Soodeh; Rezaeimanesh, Nasim; Togha, Mansoureh; Ghorbani, Zeinab; Khadem, Ebrahim; Noormohammadi, Morvarid; Torkan, Zahra (Iranian Journal of Child Neurology, 2022)
Abstract Objective Migraine is recognized as a disease with unknown etiology andvarious pathophysiologic pathways which are not fully understood. Due to the relation between dairy intake and various chronic conditions in children and also the paucity of data on the probable role of dairy intake on pediatrics’ odds of having migraine, this study was designed. Materials & Methods The present study was a population-based case-control design that was accomplished in a tertiary headache clinic.290 child (aged from7 to 14 years old) was included in this study. A definite diagnosis of migraine was performed by a neurologist; concerning the 2018 international classification of headache disorder 3 (ICHD3) criteria. Also, demographic and anthropometric characteristics were obtained. In addition, the usual dietary intake of participants was evaluated using a validated semi-quantitative food frequency questionnaire (FFQ). Results Those children in the case group significantly had higher age and BMI means (P.value:0.000). In the second regression model, odds of migraine were 48% (OR: 0.52; 95%CI:0.27-1.00) diminished in the second tertile and 53% (OR:0.47;95%CI:0.24-0.92) in the third tertile of low-fat dairy intake (P-trend:0.03). In the fully adjusted model, the achieved migraine ORs were as followings:0.48 (95% CI:0.240.95) in the second tertile and 0.46 (95% CI:0.21-0.96) in the third tertile (P-trend:0.04), respectively. Children with more high fat dairy intake also consumed higher amounts of energy, pastries, simple sugar, unhealthy snacks, and hydrogenated oil (P<0.05). Conclusion This study results proposed that a greater amount of lowfat dairy intake may attenuate the odds of having migraine attacks in pediatrics and adolescents who might be at risk of headache, which can be attributed to the micronutrient and also to the bioactive content of these dietary components.